THE IMPACT OF MUSIC ON OUR NATIONAL SPIRITUALITY (Academia Science Repository, 2023)
Music plays an important role in the development of our national spirituality. This is one of the most ancient and at the same time directions of national musical art, widespread among the people and deeply embedded in their lives. Music also reflects reality. The influence of music on our national spirituality is so great that science has already proven that it can be used to heal the sick.